Resenha de: Historia de Galicia - Vallejo, Sara Ozores (Revista de História, 1975)
RISCO (Vicente). — Historia de Galicia, 2. a ed., Vigo, Ed. Galaxia, 1971, 1ª ed. 1952), 265 p., in 8º (18 x 11,5), 2 mapas.